2013
DOI: 10.1159/000353384
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Antibodies, Activated Platelets and Serum Leptin in Childhood Immune Thrombocytopenic Purpura

Abstract: Background/Aim: The aim of this study was to evaluate the levels of platelet-associated antibodies (PAIgG and PAIgM), activated platelets and serum leptin in children with acute immune thrombocytopenic purpura (ITP). Methods: The study included 40 patients with ITP and 40 healthy age- and sex-matched controls. PAIgG, PAIgM and activated platelet levels were estimated by flow cytometry, and serum leptin levels were estimated by ELISA. Results: Activated platelets and serum leptin were significantly higher in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Badrawy et al . in a controlled study of 40 children with ITP found increased percentages of both IgG‐ and IgM‐positive platelets, with the highest IgG percentages in children with prolonged duration and the highest IgM percentages in those with brief duration. The selection of patients, technical details and the presentation of results in these studies make comparison with our findings difficult.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Badrawy et al . in a controlled study of 40 children with ITP found increased percentages of both IgG‐ and IgM‐positive platelets, with the highest IgG percentages in children with prolonged duration and the highest IgM percentages in those with brief duration. The selection of patients, technical details and the presentation of results in these studies make comparison with our findings difficult.…”
Section: Discussionmentioning
confidence: 96%
“…This finding suggests that elevation of PAIG causes some degree of platelet dysfunction from blocking of functional surface antigens. Levels of free CD‐antigens are reduced on antibody‐coated platelets , and the number of GP IIb/IIIa binding sites are lower in patients with ITP than in healthy controls . PAIgG and PAIgM possibly block functional GP IIb/IIIa receptors on the platelet surface, but the relationship between PAIG and platelet dysfunction in ITP has not yet been investigated .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, immune cell-derived leptin could act as an autocrine and/or paracrine signal that can enhance the action of leptin through the leptin receptor expressed on immune cells. Elevated levels of circulating leptin have also been associated with acute infections [ 24 ] and certain autoimmune diseases, including immune thrombocytopenia (ITP) [ 25 , 26 , 27 , 28 ]. It has previously been suggested that leptin plays an important role in the pathogenesis of ITP, and it has been proposed as a potential treatment target [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of circulating leptin have also been associated with acute infections [ 24 ] and certain autoimmune diseases, including immune thrombocytopenia (ITP) [ 25 , 26 , 27 , 28 ]. It has previously been suggested that leptin plays an important role in the pathogenesis of ITP, and it has been proposed as a potential treatment target [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%